Post-Traumatic Growth Experiences Of Bullying Victims - Arifin, Muhammad Samsul; Zunia, Elka Tiara; Ni’mah, Siti Khoirun; Wulandari, Fuji Juliana; Maqfiroh, Reni Lailatul; Faruq, Faruq (Academic Journal of Psychology and Counseling, 2023)
The study of post-traumatic growth (PTG) in bullying victims is an effort to understand how individuals can grow and develop after experiencing trauma due to acts of bullying. This study aimed to understand the experience of PTG in victims of physical, verbal, and cyberbullying, and factors that influence an individual's ability to experience PTG after bullying. This study used a phenomenological approach and data collection techniques through in-depth interviews. Five informants were selected using the purposive sampling technique based on criteria relevant to the research including university students, who had experienced bullying and trauma, and had achieved post-traumatic growth. The results showed that bullying could trigger a process of reflection, meaning-making, and emotional growth that led to positive changes in the victim, such as developing a stronger, independent, and confident attitude. The study also revealed that a supportive social environment is very important in helping bullying victims achieve PTG.